Occurence and pathogenicity of rice root-knot nematode (Meloidogyne graminicola) and varietal reaction of onion (Allium cepa) - Gergon, E. B. (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2001)
The distribution of the rice root-knot nematode, Meloidogyne graminicola, in major rice-onion farms in 4 provinces of Luzon in the Philippines (Ilocos Norte, Pangasinan, Nueva Vizcaya and Nueva Ecija), its pathogenicity, and the reaction of different onion (Allium cepa L.) cultivars to the nematode were assessed. The nematode was detected in all 17 ricefields surveyed in 4 barangays (villages) in San Jose City, Nueva Ecija and in 72% of the onion-growing areas in 78 barangays in four provinces. Galling in onion was more abundant in 'Yellow Granex' than in 'Tanduyong' and 'Batanes'. Severely infected 'Yellow Granex' developed short roots with galls and no bulbs. All 30 cultivars or lines of Allium cepa evaluated for resistance in the greenhouse supported nematode reproduction. With gall index of 5.0 and reproductive indices higher than 5.0, 'BSS-133', '1576 (lot 576 E5)', 'Dessex 38009', 'Henry's special', 'LD 959 A05', 'Sunsweet (1504)', 'Primero 37053', 'Dehydrator No. 3', and 'Yellow Granex' Improved (PRR) were found highly susceptible to M. graminicola.